How to be an efficient asynchronous neighbourhood discovery protocol in opportunistic cognitive wireless networks. (2015) - Romaszko, Sylwia; Torfs, Wim; Mähönen, Petri; Blondia, Chris
In opportunistic cognitive radio networks (CRNs) there is a need of on-demand searching for a control traffic channel by cognitive radio (CR) users in order to be able to initiate a communication. The neighbourhood discovery (ND) phase is challenging due to the dynamics of such networks. Lately, there has been a proliferation of different RDV protocols. However, most protocols have a narrow focus, which is usually a RDV guarantee in a single cycle. Very rarely asynchronism is exploited as a main factor, or considering channel heterogeneity in terms of quality. In this study we show how to add and benefit from an asynchronous RDV extension and its enhancement. Thanks to induced asynchronism, the ranking of channels is introduced, allowing nodes to stay longer on better quality channels. We analyse the behaviour of different selected ND protocols in terms of time-to-rendezvous and normalised RDV. We show that an asynchronism significantly improves the efficiency of the studied protocols.